Generalized and specific anxiety in adolescents following heart transplant. (29th December 2019) - McCormick, Amanda D.; Schumacher, Kurt R.; Zamberlan, Mary; Uzark, Karen; Yu, Sunkyung; Lowery, Ray; Rottach, Nichole; Cousino, Melissa K.
Abstract: Mental health concerns are associated with worse outcomes after adult heart transplant. Illness‐specific anxiety is associated with worsened psychological well‐being after other solid organ transplants but has never been characterized after pediatric heart transplant. This single‐center cross‐sectional study aimed to evaluate illness‐specific and generalized anxiety after heart transplantation in adolescents. A novel 12‐item PHTF, GAD‐7, and the PedsQL were administered. Univariate associations of demographics, clinical features, and medication adherence as measured by immunosuppression standard deviation with the PHTF and GAD‐7 scores were evaluated. Internal consistency and validity of the PHTF were examined. In total, 30 patients participated. The most common illness‐specific fears were retransplantation, rejection, and more generally post‐transplant complications. The PHTF had good internal consistency (Cronbach α  = .88). Construct validity was demonstrated between PHTF and GAD‐7 ( r  = .62) and PedsQL ( r  = −.54 to −.62). 23% endorsed moderate to severe generalized anxiety symptoms. More severe symptoms were associated with older age at survey ( P  = .03), older age at listing ( P  = .01) and having post‐transplant complications ( P  = .004). Patients with moderate or severe symptoms were more likely to report late immunosuppression doses ( P  = .004). Illness‐specific and generalized anxiety may be prevalent after pediatric heart transplant. Screening for anxiety in adolescents post‐transplant may identify those at risk for adverse outcomes including non‐adherence. The PHTF is a brief, valid, and reliable instrument identifying illness‐specific anxiety in this population.